PERUBAHAN DARI KABUPATEN LIMBANGAN KE KABUPATEN GARUT (1813-1942) - farizal hami; Samsudin farizal hami (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2021)
ABSTRAKThe results of research on the Change from Limbangan Regency to Garut Regency, which in it discusses the History of the Name of the City of Garut, the History of the Entry of Islam to Garut Regency, the Cultural Heritage of Garut, and Tourism and Leading Potential in Garut Regency The purpose of this research is to improve knowledge about Garut. By conducting heuristic research methods, criticism, interpretation and historiography, it is hoped that we can see more closely the background about Garut. The sources used, namely from books, journals, and interviews, with the study of the closest library, namely the Garut library, and the Garut district culture and tourism service, and field work. The conclusion of this study shows that before becoming Garut district, it was Limbangan district which was replaced by GG Daedenles. Also the first time Islam came to Garut district was brought by Arif Muhammad or who is often called the Embah Dalem Arif Muhammad, he was a Mataram soldier who fled because of his failure to attack the VOC in Batavia, because he was afraid to be angry and cancel, finally he decided to run to Cangkuang Temple, Knampung Pulo and Islamic school there. There are also busaya heritages that are very famous and become a characteristic of Garut district, one of which is the Garutsquare there is a building whose name is Babwisata this place is used for ceremonial officials. And there is also tourism and the potential for excellence in the famous Garut district, one of which is beach tourism in Garut, the superiority of the sheep owned by Garut district.